Crossability of miniature rose and quantitative and qualitative traits in hybrids - Meral, Ezgi Doğan (Frontiers in Plant Science, 2023)
Six divergent popular pot miniature rose as female parent, Rosa centifolia and Black Baccara as male parent rose and 190 of their F1 hybrids were studied to determine the extent of crossability and heterosis effects for several quantitative and qualitative traits for determining miniature rose breeding potential. The percentage of pollen viability and pollen germination rate differed between 48,61%-61,27% and 23,26%-32,19% respectively. All cultivars exhibited a strong correlation between fruit set, the weight of fruit, total set, the weight of seed, the number of seeds per fruit, and seed germination rate. The cultivar Rosa White Star as a female parent exhibited good fruit set and crossing success while Juanita Kordana showed poor crossing success rates. The maximum setting of fruits (75%), total seed (132 seeds), and weight of seed (0,68 g) after the crossing was Rosa White Star x R. centifolia. The highest number of seeds per fruit (12,63) was obtained from Rosa Bling Love Star x R. centifolia and the Red Romance x Black Baccara had the maximum germination of seed rate (48%). The potential for heterobeltiosis and heterosis were variable and exhibited contrasting performance for various qualitative and quantitative traits between F1 progenies. The parents and F1 hybrids were sorted into three major groups by cluster analysis based on phenotypic variation.